The challenges on out-scaling participatory methods in agricultural research - Aw-Hassan, Aden A. (2005)
For the last decade or so, participatory research has become an attractive mechanism for conducting adaptive agricultural research. This is mainly motivated by the perception that closer association with resource-poor farmers in identifying the problem and involving them in research implementation presents greater chance of success and adoption of research outputs; hence; enhancing the impact of agricultural research. The advantage of participatory research is considered more prominent in, although not limited to, the adaptation of technologies that require local knowledge of the social, economic and biophysical environments or need high level of human capital or require cooperation of different stakeholders. Resource-poor households in the dry and marginalized areas who face complex biophysical and socioeconomic constraints have benefited less from the agricultural research successes, which led to the green revolution, compared to the farmers in well endowed environments. The result is high prevalence of poverty and malnutrition in the dry areas. However, there is potential to improve the welfare of these households through agricultural research and development. The development of participatory research approach and its application came form the necessity of reaching out these resource-poor farmers whom their participation in the research and development process is considered as key in bringing about a desirable change.